2015
DOI: 10.1007/s10916-015-0294-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Based Smart Health Monitoring System for Automatic Cardiovascular and Fall Risk Assessment in Hypertensive Patients

Abstract: The aim of this paper is to describe the design and the preliminary validation of a platform developed to collect and automatically analyze biomedical signals for risk assessment of vascular events and falls in hypertensive patients. This m-health platform, based on cloud computing, was designed to be flexible, extensible, and transparent, and to provide proactive remote monitoring via data-mining functionalities. A retrospective study was conducted to train and test the platform. The developed system was able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…The symbol () indicates that the research paper uses the checked technology and the opposite is indicated by the symbol (). [15] Chronic diseases [2] Cardiovascular [26] Heart diseases [152] Ubiquitous monitoring system [28] Pain assessment [29] Heart diseases [40] Knees rehabilitation [153] Vital signs gathering and processing [46] Chronic diseases [47] Hypertension [57] Tracking daily activities [61] EXP carried on healthy volunteers [92] Context aware monitoring [77] Diabetes and Diet monitoring [96] Heart diseases [97] Diabetes [90] Diabetes [93] Mental disorder [154] Chronic diseases [155] Monitor patients with depression [131] Cardiovascular diseases [156] Hypertension, hypotension [157] Diabetes [158] Heart diseases [159] Knee arthroplasty [160] Elderly [161] Diabetes [162] Parkinson's disease [106] Fall detection [117] Diabetes [116] Alzheimer's Currently, many health monitoring projects and applications have been initiated that use different architectures. Health monitoring systems are heterogeneous and have been developed for various diseases and disabilities.…”
Section: Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symbol () indicates that the research paper uses the checked technology and the opposite is indicated by the symbol (). [15] Chronic diseases [2] Cardiovascular [26] Heart diseases [152] Ubiquitous monitoring system [28] Pain assessment [29] Heart diseases [40] Knees rehabilitation [153] Vital signs gathering and processing [46] Chronic diseases [47] Hypertension [57] Tracking daily activities [61] EXP carried on healthy volunteers [92] Context aware monitoring [77] Diabetes and Diet monitoring [96] Heart diseases [97] Diabetes [90] Diabetes [93] Mental disorder [154] Chronic diseases [155] Monitor patients with depression [131] Cardiovascular diseases [156] Hypertension, hypotension [157] Diabetes [158] Heart diseases [159] Knee arthroplasty [160] Elderly [161] Diabetes [162] Parkinson's disease [106] Fall detection [117] Diabetes [116] Alzheimer's Currently, many health monitoring projects and applications have been initiated that use different architectures. Health monitoring systems are heterogeneous and have been developed for various diseases and disabilities.…”
Section: Study Resultsmentioning
confidence: 99%
“…This system gathered all the vital signs sensed by biosensors and automatically uploaded them to a cloud service (Xively), permitting physicians and other caregivers to remotely monitor patients in real-time. The same idea is in [ 47 ], where the authors provided a monitoring system for heart diseases. This system provided real-time monitoring and predicted future risk over the next 12 months using data mining techniques.…”
Section: Main Components Of the Rpm Systemmentioning
confidence: 99%
“…In CDDS envisioned end-users are not only experienced cardiologists, but also patients, caregivers, general practitioners, nurses, trainees, and so forth. Moreover, once trained, the network responds in a very short time and can be embedded into mobile phones or deployed to cloud architectures, as we already discussed elsewhere [13,55].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, such a system provides a feasible solution to the increasing demand for long-term care support and monitoring to community-dwelling elderly individuals who may have difficulties in accessing health services [ 13 - 16 ]. A review of the current literature showed that telehealth systems have been assisting older adults in specific health-related areas such as chronic conditions [ 17 - 22 ], falls [ 23 , 24 ], and general wellness [ 25 - 28 ]. For example, Or and Tao [ 19 ] developed a patient-centered, tablet computer-based self-monitoring system to enable older adults with type 2 diabetes and hypertension to measure and monitor their blood glucose and blood pressure.…”
Section: Introductionmentioning
confidence: 99%